Uresničevanje Nacionalnega gozdnega programa na področju razvoja podeželja, podpore lastnikom gozdov in ozaveščanje javnosti - Breznikar, Andrej (Gozdarski vestnik, 2014)
The article presents realization of the National Forest Programme in the fields linked to rural area development, forest owners and awareness-raising of the public concerning importance and role of forests in forestry. Listed are: evaluation of realization of individual goals in these fields, role of Slovenia Forest Service in realization of individual goals and evaluation of individual indicators we use for measuring realization of individual goals.
Keywords: Nacionalni gozdni program; razvoj podeželja; lastniki gozdov; splošna javnost; Zavod za gozdove Slovenije